Persistent gaps in the prevention of mother-to-child HIV transmission in central Uganda: a case-control study - Gloria Lubega; Benard Kikaire; Michael Mubiru; Violet Ankunda; Wilber Ssembajjwe; Samuel Bengo; Moses Kibirige; Joseph Lutaakome; Sylvia Kusemererwa; Andrew Abaasa; Eugene Ruzagira (International Health, 2026)
Abstract Objectives Achieving elimination of mother-to-child transmission (eMTCT) remains a challenge in sub-Saharan Africa. Identifying persistent risk factors is critical for addressing remaining gaps in the prevention-of-mother-to-child HIV transmission (PMTCT) cascade. Methods We conducted a case-control study among mother-child pairs where cases were mothers of HIV-positive children aged <6 years, while controls were mothers of HIV-exposed but HIV-negative children aged <6 years. Data were collected on sociodemographic characteristics, antiretroviral therapy (ART), antenatal care (ANC), infant-feeding practices, and partner involvement. Logistic regression identified factors independently associated with being a case. Results A total of 183 mothers (91 cases and 92 controls) were included, with a median age of 30.9 (IQR 27.0–36.0) years. Attending <4 ANC visits (aOR 2.58; 95% CI 1.07–6.22) and mixed feeding before 6 months (aOR 5.56; 95% CI 2.22–13.94) were significantly associated with increased odds of MTCT. Child age ≥4 years (aOR 5.65; 95% CI 2.36–13.51) was associated with HIV-positive status. ART duration >5 years (aOR 0.07; 95% CI 0.03–0.18) and partner support (aOR 0.20; 95% CI 0.07–0.59) were strongly protective. Conclusion Residual MTCT remains associated with modifiable factors across the PMTCT cascade. Strengthening early and sustained ANC attendance, partner involvement, exclusive breastfeeding, and ART retention may accelerate progress towards eMTCT.